Além dos 90 minutos: uma etnografia da mediatização no Estádio Beira Rio - Martins, Marcel Neves (Universidade do Vale do Rio dos Sinos, 2011)
This dissertation introduces a study made at the Beira-Rio Stadium, in Porto Alegre, about the social mediatization the operate - by interational procedures - on the game`s 90 minuts. To achieve it, fourteen deslocations for field work were made over a period of seven months. Etnography was the data collection method; Through participating observation technique we went through the bleacher sections, press' room and booths; in those, we visited writen press booths, Rádio Guaiba e RBS TV. To realize the social mediatization by the relations between sports and media fields we size the games realities in three parts. At first, we consider that three moments are involved in the disputes, before, during and after the matches. Second part shows Sport Club Internacional running according to the media logics. At last, Print, radio and TV press modes of operation are known at the football matches coverage.
Keywords: Mediatização; Sport Club Internacional; Esporte; Mídia; Imprensa; Mediatization; Sports; Media; Press; ACCNPQ::Ciências Sociais Aplicadas::Comunicação